2009
DOI: 10.1080/08941930902866279
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Total or Near-Total Bilateral Thyroidectomy for the Treatment of Bilateral Multinodular Goiter

Abstract: It is safe and feasible to perform either total or near-total thyroidectomy in patients with bilateral multinodular goiter. These treatments provide decisive advantages over partial and subtotal thyroidectomies in terms of the recurrence and reoperation rate with comparable postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Although it is not possible to calculate the true recurrence rate for BMNG requiring reoperation from the data reported, other studies have reported reoperation rates as high as 26 per cent 21,22 . Some 23 years after the change of policy to total thyroidectomy as the treatment of choice for BMNG, the incidence of secondary thyroidectomy in the authors' unit has declined such that less than 0·5 per cent of the total thyroid clinical workload is bilateral reoperative surgery for BMNG.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not possible to calculate the true recurrence rate for BMNG requiring reoperation from the data reported, other studies have reported reoperation rates as high as 26 per cent 21,22 . Some 23 years after the change of policy to total thyroidectomy as the treatment of choice for BMNG, the incidence of secondary thyroidectomy in the authors' unit has declined such that less than 0·5 per cent of the total thyroid clinical workload is bilateral reoperative surgery for BMNG.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study by Yang et al on the feasibility of TT for MNG in comparison with less extensive surgery, there was no difference between TT and less extensive thyroid surgery with respect to early and late complications; however, the recurrence rates after 3 years of follow-up were signifi cantly higher after partial or subtotal thyroid surgery (6.7% vs 0%). 11 Moreover, TT achieves complete remission of symptoms, rules out malignancy, and has low morbidity and mortality rates. It is a defi nitive etiological treatment that prevents recurrence and thus should be selected as the surgical technique for nodules on the posterior side of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…4). According to 3 included studies [12,13,14], the mean recurrence rate in BST was 10.0% (44/441), and TT faired significantly better than BST in terms of the frequency of recurrence. Therefore, TT was considered to be a valuable option for BMNG.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 3 included studies [12,13,14] reported levothyroxine requirements following thyroidectomy. Biological hypothyroidism occurred on average 5.6 months after surgery [41].…”
Section: Discussionmentioning
confidence: 99%